2006
DOI: 10.1071/mf05046
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in major ions, nutrients and chlorophyll a at two sites in the Swan River estuary, Western Australia

Abstract: Seasonal variations in major ions, nutrients and chlorophyll a were examined at two sites in the upper reaches of the Swan River estuary, Western Australia. Intra-annual variations between the variables were strongly influenced by seasonal riverine discharge, though major ions behaved highly conservatively across a wide range of salinity. Reduced discharge following winter produced strong density stratification that coincided with upstream salt wedge propagation and produced distinct physico-chemical identitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Although human development has converted the once extensive wetlands and forest that occupied the Swan Coastal Plain into urban, residential, and agricultural land, the legacy of the native landscape persists as a large source of DOM to river and estuarine ecosystems (Petrone 2010 Estuarine DOM and nutrient concentrations showed strong seasonal variability that was largely controlled by changes in river flow and the delivery of dissolved materials from adjacent catchments (Chan and Hamilton 2001;Hamilton et al 2006;Petrone 2010). For example, NO 3 accounted for the greatest fraction of TN during the winter months of July and August, consistent with previous research of Swan-Canning catchments that has shown large winter NO 3 fluxes from diffuse N sources across forested and agro-urban catchments (Petrone 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although human development has converted the once extensive wetlands and forest that occupied the Swan Coastal Plain into urban, residential, and agricultural land, the legacy of the native landscape persists as a large source of DOM to river and estuarine ecosystems (Petrone 2010 Estuarine DOM and nutrient concentrations showed strong seasonal variability that was largely controlled by changes in river flow and the delivery of dissolved materials from adjacent catchments (Chan and Hamilton 2001;Hamilton et al 2006;Petrone 2010). For example, NO 3 accounted for the greatest fraction of TN during the winter months of July and August, consistent with previous research of Swan-Canning catchments that has shown large winter NO 3 fluxes from diffuse N sources across forested and agro-urban catchments (Petrone 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, peaks in NH 4 and TP concentrations also coincided with the advance of the salt wedge into the middle and upper estuary. Substantial longitudinal movement of the salt wedge occurs seasonally in the SwanCanning estuary (Kurup et al 1998), and density stratification can cause benthic anoxia and regeneration of nutrients leading to NH 4 and SRP accumulation in bottom waters (Thompson 1998;Hamilton et al 2006). As the salt wedge advances upriver, the dense saline water can displace anoxic bottom waters or interstitial sediment pore water and release N and P into the water column, which in turn, may support algal blooms (Twomey and John 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, environmental systems and estuaries in particular are inherently dynamic and complex; water flow rate and direction can vary significantly with both tidal and precipitation inputs (Hamilton et al, 2006;Haralambidou et al, 2010). Estuaries are also typically heterogeneous, with density stratification of the water column often leading to at least two layers of water characterised by fundamentally different geochemical properties (e.g., salinity, dissolved oxygen, pH) (Stephens and Imberger, 1996;Kurup et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, an analysis based on the seasons of the year showed that the flows are always from the estuary to the sea, except for the phytoplankton community (Chlorophyll-a and the pico-nanoplankton and microplankton fractions), where an inverse flow occurs during the dry season. According to de Miranda et al (2002) and Hamilton et al (2006), the lateral shear can be sufficiently intense in narrow estuarine channels to generate homogeneous conditions. Under these conditions, the salinity gradually increases in the direction of the sea, and the mean movement is oriented in that direction at all depths.…”
Section: Discussionmentioning
confidence: 99%